Impact of the Collaborative Pharmaceutical Care at Tallaght Hospital (PACT) model on medication appropriateness of older patients. Issue 1 (18th June 2015) - Tallon, Maria; Barragry, John; Allen, Ann; Breslin, Niall; Deasy, Evelyn; Moloney, Eddie; Delaney, Tim; Wall, Catherine; O'Byrne, John; Grimes, Tamasine
Abstract : Objectives: A high prevalence of potentially inappropriate prescribing (PIP) has been identified in older patients in Ireland. The impact of the Collaborative Pharmaceutical Care at Tallaght Hospital (PACT) model on the medication appropriateness of acute hospitalised older patients during admission and at discharge is reported. Methods: Uncontrolled before-after study. The study population for this study was medical patients aged ≥65 years, using ≥3 regular medicines at admission, taken from a previous before-after study. Standard care involved clinical pharmacists being ward-based, contributing to medication history taking and prescription review, but not involved at discharge. The innovative PACT model involved clinical pharmacists being physician team-based, leading admission and discharge medication reconciliation and undertaking prescription review, with authority to change the prescription during admission or at discharge. The primary outcome was the Medication Appropriateness Index (MAI) score applied pre-admission, during admission and at discharge. Results: Some 108 patients were included (48 PACT, 60 standard). PACT significantly improved the MAI score from pre-admission to admission (mean difference 2.4, 95% CI 1.0 to 3.9, p<0.005), and from pre-admission to discharge (mean difference 4.0, 95 CI 1.7 to 6.4, p<0.005). PACT resulted in significantly fewer drugs with one or more inappropriate rating at discharge (PACT 15.0%, standard 30.5%, p<0.001). The MAI criteria responsible for most inappropriate ratings were 'correct directions' (4.8% PACT, 17.3% standard), expense (5.3% PACT, 5.7% standard) and dosage (0.6% PACT, 4.0% standard). PACT suggestions to optimise medication use were accepted more frequently, and earlier in the hospital episode, than standard care (96.7% PACT, 69.3% standard, p<0.05). Conclusions: Collaborative pharmaceutical care between physicians and pharmacists from admission to discharge, with authority for pharmacists to amend the prescription, improves medication appropriateness in older hospitalised Irish patients.